The Effect of Lycopene Preexposure on UV-B-Irradiated Human Keratinocytes. (17th November 2015) - Ascenso, Andreia; Pedrosa, Tiago; Pinho, Sónia; Pinho, Francisco; Oliveira, José Miguel P. Ferreira de; Cabral Marques, Helena; Oliveira, Helena; Simões, Sandra; Santos, Conceição
Abstract : Lycopene has been reported as the antioxidant most quickly depleted in skin upon UV irradiation, and thus it might play a protective role. Our goal was to investigate the effects of preexposure to lycopene on UV-B-irradiated skin cells. Cells were exposed for 24 h to 10 M lycopene, and subsequently irradiated and left to recover for another 24 h period. Thereafter, several parameters were analyzed by FCM and RT-PCR: genotoxicity/clastogenicity by assessing the cell cycle distribution; apoptosis by performing the Annexin-V assay and analyzing gene expression of apoptosis biomarkers; and oxidative stress by ROS quantification. Lycopene did not significantly affect the profile of apoptotic, necrotic and viable cells in nonirradiated cells neither showed cytostatic effects. However, irradiated cells previously treated with lycopene showed an increase in both dead and viable subpopulations compared to nonexposed irradiated cells. In irradiated cells, lycopene preexposure resulted in overexpression of BAX gene compared to nonexposed irradiated cells. This was accompanied by a cell cycle delay at S-phase transition and consequent decrease of cells in G0/G1 phase. Thus, lycopene seems to play a corrective role in irradiated cells depending on the level of photodamage. Thus, our findings may have implications for the management of skin cancer.